Port designer's handbook : recommendations and guidelines - Thoresen, Carl A. (Thomas Telford, 2003)
This handbook reflects the lastest progress and developments in navigation safety, port planning and site selection, layout of container, oil and gas terminals, cargo handling, berth design and construction, fender and mooring principles.